Imagining Japan: the Japanese tradition and its modern interpretation - Bellah, Robert N. (University of Californiarnia Press, 2003)
The contemporary meaning of Kamakura Buddhism -- Ienaga Saburo and the search for meaning in modern Japan -- Japan's cultural identity: some reflections on the work of Watsuji Tetsurō -- Notes on Maruyama Masao -- Intellectual and society in Japan -- The Japanese emperor as a mother figure -- Continuity and change in Japanese society